PENGETAHUAN SIKAP REMAJA TENTANG PENGGUNAAN NARKOBA DI KOMPLEK SIDIMPUAN BARU KELURAHAN SILANDIT KOTA PADANGSIDIMPUAN - ., Mansursyah; Imsaruddin, Guntur (Jurnal Kesehatan Ilmiah Aufa Royhan, 2018)
Narcotics and drugs is substance or indigenous doctor plant or not plant, well sintesisand also sintesis half decrease causative or consciousness change, removing taste, reduceuntil removes agonies, and gets to evoke dependency. This research intent to knowAdolescent Attitude Science About dikomplek Sidimpuan's Narcotics And Drugs Purposesub-district New Silandit Padangsidimpuan's City Year 2016. This research constituteresearch that gets quantitative descriptive character with approaching cross sectional .This observational sample as much 37 dikomplek sidimpuan's striplings sub-district newsilandit. Determination foots up sample base full scale sampling. Of 37 respondentmajority respondents utilize narcotics and drugses as much 19 person (51,4%) and thefew respondent not utilize narcotics and drugs as much 18 person (48,6%). Base scienceof statistic quiz is gotten assesses p=0,013 (p<0,05) its mean h 0 accepted h a refused bymatter no influence among gnostic to adolescent action about narcotics and drugspurpose. Base attitude of statistic quiz gotten by nulai p=0,001 (p<0,05) its mean h 0refused h a accepted by matter available influence among gnostic to adolescent actionabout attitude to adolescent action. Expected to do research about adolescent attitude science about narcotics and drugs purpose at in contrast to place greater populationamount so gets to complete this research